2008
DOI: 10.4049/jimmunol.180.6.3833
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity to Itk Kinase Signals for T Helper 2 Cytokine Production and Chemokine-Mediated Migration

Abstract: Allergic asthma is dependent on chemokine-mediated Th2 cell migration and Th2 cytokine secretion into the lungs. The inducible T cell tyrosine kinase Itk regulates the production of Th2 cytokines as well as migration in response to chemokine gradients. Mice lacking Itk are resistant to developing allergic asthma. However, the role of kinase activity of Itk in the development of this disease is unclear. In addition, whether distinct Itk-derived signals lead to T cell migration and secretion of Th2 cytokines is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…97 Many studies have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 26 demonstrated that ITK is essential for the control of T helper 2 (Th2) responses and pathological conditions such as lung inflammation, eosinophil infiltration, and mucous production. 98 Consequently, ITK is a therapeutic target for the development of drugs to treat allergic asthma and inflammatory disorders.…”
Section: Interleukin-2 Inducible T-cell Kinase (Itk) Inhibitor 70mentioning
confidence: 99%
“…97 Many studies have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 26 demonstrated that ITK is essential for the control of T helper 2 (Th2) responses and pathological conditions such as lung inflammation, eosinophil infiltration, and mucous production. 98 Consequently, ITK is a therapeutic target for the development of drugs to treat allergic asthma and inflammatory disorders.…”
Section: Interleukin-2 Inducible T-cell Kinase (Itk) Inhibitor 70mentioning
confidence: 99%
“…Despite relatively normal number (trending the lower range) of CD8 + αβ T cells, Itk −/− mice exhibited CD4 + αβ T-cell lymphopenia, with reduced proportion of naive and increased memory αβ T cells (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). In the absence of Itk, mouse CD4 + T cells are impaired in Th2 (producing IL-4/5/13) (32)(33)(34)(35)(36)(37)(38), Th9 (producing IL-9) (39), Th17 (producing IL-17) (35,(40)(41)(42), and Tr1 (producing IL-10) cell responses (43), while they are enhanced in Th1 (producing IFN-γ) cell response (32,34,38,44,45). Analysis of Itk −/− mice also reveals altered γδ T-cell development (46)(47)(48)(49); however, the presence and function of γδ T cells has not been evaluated in ITKdeficient humans.…”
Section: Introductionmentioning
confidence: 99%
“…(47) showed by employing Itk ‘kinase‐dead’ mutants that the kinase activity of Itk is important for the activation of T cells. The latter observation is supported by experiments showing that Itk kinase activity is central to the development of inflammation in murine models of allergic asthma (48). Although we cannot rule out that Itk in part contributes to T‐cell activation via a scaffolding function, the use of the quite selective small molecule inhibitor, Compound 44, reveals that modulating the kinase activity of Itk has clear anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 76%